Design and Development of a Web-Based Medicine Inventory Information System: Case Study on One of The Pharmaceutical Distribution Companies in Bandung - Rahadian, Muhamad Rizki; Supriatna, Ade; Risanti, Rini; Retnowaty, Agung Tri (Informatics Management, Engineering and Information System Journal, 2023)
The establishment of this company took place in 2011, and it currently has a workforce of 63 individuals. The company distributes goods exclusively to authorized agencies or pharmacies rather than the general public. Only entities with a valid business license can purchase drugs from this company. It should be noted that this company does not produce drugs but rather acquires them from suppliers for resale. There are still challenges in gathering reports on the inflow and outflow of medicine stock data during inventorying. These reports are still reliant on ledger records. Consequently, warehouse staff require considerable time to document reports regarding the arrival and departure of items. This study aims to examine and create a web-based system for managing drug inventory, which is essential for enterprises. Developing this system entails utilizing the Prototyping methodology as a system development approach and the Unified Modeling Language (UML) as a modeling instrument. The activities implemented in this system encompass the management of goods data, incoming goods transactions, outgoing goods transactions, inventory management, goods stock reports, outgoing goods reports, incoming goods reports, and user administration. Based on this study, a web application was developed to address the drug supply system issues at Pharmaceutical Distribution Companies In Bandung.